Silicon-carbon composite for negative electrode material of secondary battery and preparation method of silicon-carbon composite
By using nano-silicon particles and high-softening point asphalt, the pore structure is optimized, and the structural damage caused by volume expansion of the silicon material of the secondary battery negative electrode material is solved, and the initial discharge capacity, efficiency and life of the battery are improved.
Patent Information
- Application Number
- CN202380060466.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-07-26
- Publication Date
- 2025-03-28
AI Technical Summary
The theoretical capacity of the existing negative electrode material of secondary batteries is limited, and non-graphite materials such as silicon expand severely during charging and discharging, resulting in structural damage and short life.
Silicon-asphalt composites containing nanosilicon particles and high-softening point bitumen are used to prepare silicon-carbon composites through the carbonization process, and the pore size and proportion are optimized to improve the initial discharge capacity, initial efficiency and life characteristics of the secondary battery.
By optimizing the pore structure, the initial discharge capacity, initial efficiency and life characteristics of the secondary battery are improved, and the structural damage caused by volume expansion of silicon material during charging and discharging is solved.
Smart Images

Figure CN119731804A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon-carbon composite for a negative electrode material of a secondary battery and a preparation method thereof, which can improve the initial discharge capacity (IDC), initial efficiency (ICE) and life characteristics of the secondary battery. Background Art
[0002] The performance improvement of secondary batteries is based on structural elements such as positive electrode materials, negative electrode materials, and electrolytes.
[0003] Among the above structural elements, graphite materials mainly used as negative electrode materials are commercially used due to their excellent electrochemical characteristics and low cost. However, their theoretical capacity is limited to 370 mAh / g, so their application in high-capacity secondary batteries is limited.
[0004] In order to overcome the above limitations, non-graphite negative electrode materials such as silicon, tin, and germanium are increasingly emerging as alternative materials. Among them, the theoretical capacity of silicon is 4000-4200 mAh / g, which is almost 10 times higher than that of graphite, so it has attracted much attention as a graphite substitute. However, compared with the high theoretical capacity, the large volume expansion of up to about 400% during the charge and discharge process has the disadvantages of structural destruction of the material and low life.
[0005] As a method for alleviating the volume expansion of silicon, a method of preparing a composite by mixing a carbon material has been proposed. The important issue of using the composite as a negative electrode material for a secondary battery to improve the performance of the secondary battery is becoming increasingly prominent.
[0006] For example, a method has been developed in which a slurry containing nano silicon (Nano Si) particles is formed into spherical powder particles, and pitch is applied on the surface of the spherical powder particles as a carbon material. It is necessary to develop a high-quality silicon-carbon composite for anode materials of secondary batteries and a preparation method thereof that can further improve the initial discharge capacity, initial efficiency and life characteristics of secondary batteries by adjusting the properties of the composite using the nano silicon particles and pitch. Summary of the invention
[0007] Technical issues
[0008] An object of the present invention is to provide a secondary battery negative electrode material comprising a silicon-carbon composite prepared by using a silicon-asphalt composite comprising nano-silicon particles and a high softening point asphalt, and a method for preparing the same.
[0009] Another object of the present invention is to provide the negative electrode material for a secondary battery, the negative electrode material for a secondary battery and a secondary battery comprising the negative electrode material, so as to improve the initial discharge capacity, initial efficiency and life characteristics of the secondary battery.
[0010] The purpose of the present invention is not limited to the above-mentioned purpose. Other purposes and advantages of the present invention can be understood through the following description and can be more clearly understood through the embodiments of the present invention. Moreover, it is obvious that the purposes and advantages of the present invention can be achieved by the means and combinations thereof shown in the scope of the invention claims.
[0011] Technical Solution
[0012] According to one embodiment of the present invention, a silicon-carbon composite for secondary battery negative electrode material can be provided, which is formed by a silicon-asphalt composite comprising nano-silicon particles and high-softening point asphalt, wherein the average particle size (D50) of the nano-silicon particles is less than 150 nm, the softening point of the high-softening point asphalt is 200-300°C, and the average particle size (D50) of the high-softening point asphalt is 0.5-2 μm.
[0013] According to another embodiment of the present invention, a method for preparing a silicon-carbon composite for a secondary battery negative electrode material can be provided, comprising: step (a), mixing a high-softening point asphalt having a softening point of 200 to 300°C with a solvent, and preparing a crushed asphalt slurry (slurry) having an average particle size (D50) of 0.5 to 2 μm by wet crushing; step (b), mixing silicon particles with a solvent, and preparing a nano-silicon particle slurry having an average particle size (D50) of less than 150 nm by crushing; step (c), mixing the crushed asphalt slurry of step (a) with the nano-silicon particle slurry of step (b) to form a mixed slurry of asphalt-silicon particles; step (d), forming spherical powder particles by drying the mixed slurry of asphalt-silicon particles; and step (e), carbonizing the spherical powder particles.
[0014] According to another embodiment of the present invention, there may be provided a negative electrode material for a secondary battery, including a silicon-carbon composite prepared using the silicon-pitch composite according to one embodiment of the present invention.
[0015] Effects of the Invention
[0016] The silicon-carbon composite of the present invention as a negative electrode material for a secondary battery can have optimized pore size and proportion inside the composite, thereby improving the initial discharge capacity, initial efficiency and life characteristics of a secondary battery prepared by including the composite as a negative electrode material.
[0017] The specific effects of the present invention will be described together with the above-mentioned effects in the following description of the specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The flowchart shows a method for preparing a negative electrode material for a secondary battery according to one embodiment of the present invention.
[0019] Figure 2 and Figure 3 The graphs are for analyzing the diameters of the crushed asphalt and nano-silicon particles in Example 1 respectively.
[0020] Figures 4 to 6 Scanning electron microscope (SEM) images of the silicon-carbon composite prepared in Example 1 are respectively shown.
[0021] Figure 7 This is a graph analyzing the diameter of the crushed asphalt of Comparative Example 1.
[0022] Figure 8 Scanning electron microscope images of the silicon-carbon composite prepared in Comparative Example 1 are respectively shown.
[0023] Fig. 9 Scanning electron microscope images of the silicon-carbon composite prepared in Example 2 are respectively shown.
[0024] Fig.10 Scanning electron microscope images of the silicon-carbon composite prepared in Comparative Example 2 are respectively shown.
[0025] Fig.11 A graph showing the life characteristics of Examples 1 and 2 and Comparative Examples 1 and 2 at 50 cycles (vertical axis: specific capacity at 50 cycles, horizontal axis: number of cycles) is shown. DETAILED DESCRIPTION
[0026] The following content will describe the aforementioned objects, features and advantages in detail with reference to the accompanying drawings, and a person skilled in the art of the present invention can easily implement the technical ideas of the present invention accordingly. In the process of describing the present invention, if it is determined that the specific description of the related known technology of the present invention will confuse the gist of the present invention, its detailed description will be omitted. Below, the preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the accompanying drawings, the same reference numerals indicate the same or similar structural elements.
[0027] In this specification, descriptions of unexplained parts that can be sufficiently technically inferred by a person skilled in the art to which the present invention belongs will be omitted.
[0028] Hereinafter, when referring to the "upper part (or lower part)" of a structural element or an arbitrary structure being arranged "above (or below)" a structural element, it not only indicates that the arbitrary structure is arranged in contact with the upper side (or lower side) of the structural element, but also may indicate that other structures may be interposed between the structural element and the arbitrary structure arranged above (or below) the structural element.
[0029] Furthermore, when it is recorded that a certain structural element is “connected”, “combined” or “joined” with other structural elements, it not only indicates that the structural elements can be directly connected or joined to each other, but should also be interpreted as a situation where other structural elements are “interposed” between the structural elements, or a situation where the structural elements can be “connected”, “combined” or “joined” through other structural elements.
[0030] In this specification, a "silicon-pitch composite" refers to a composite material of a mixture of silicon and pitch, and a "silicon-carbon composite" can be described as a composite material in which pitch is converted into carbon after the silicon-pitch composite is subjected to a carbonization step.
[0031] In this specification, "average particle size" may refer to "D50" measured using a particle size analyzer (LS13 320 Laser Diffraction Particle Size Analyzer; manufactured by BECKMAN COULTER), which is used to define and measure the size of the asphalt particles, silicon ions and the ultimately prepared silicon-carbon composite in the present invention.
[0032] In this specification, the “average diameter” is used to define the size of the “pores” of the silicon-carbon composite of the present invention, and may refer to the diameter measured according to “Measurement Method 2: Pore Size and Porosity” described below in this specification.
[0033] Hereinafter, the silicon-carbon composite for secondary battery negative electrode material and the preparation method thereof of the present invention will be described in detail.
[0034] Silicon-carbon composites for negative electrode materials of secondary batteries
[0035] The silicon-carbon composite as a negative electrode material for a secondary battery according to one embodiment of the present invention can be formed from a silicon-asphalt composite containing nano silicon particles and high softening point asphalt. In order to prepare the silicon-carbon composite as a negative electrode material for a secondary battery, a process of carbonizing the silicon-asphalt composite prepared by forming a slurry prepared by mixing a composite of silicon particles and asphalt into spherical powder particles is performed.
[0036] Through the carbonization process, the silicon particles are left as a skeleton, and as the high softening point asphalt is reduced by 30% to 50% in volume (weight) during carbonization, the part where the asphalt once existed forms pores in the shape of the asphalt before carbonization and becomes carbon. In this case, if the high softening point asphalt is dissolved in a solvent to prepare a composite, the asphalt can be evenly coated on the nano silicon particles before carbonization to reduce the amount of pores generated, thereby making the final pore size smaller after carbonization and reducing the porosity.
[0037] As a result of numerous studies, the inventors have confirmed that the size of the asphalt contained in the silicon-asphalt composite used to prepare the negative electrode material for secondary batteries can be adjusted, thereby adjusting the size and proportion of the pores generated by the composite. This can further improve the performance of the battery when the finally prepared silicon-carbon composite is used as a negative electrode material for application in secondary batteries, thereby completing the present invention.
[0038] Specifically, the silicon-carbon composite as a negative electrode material for a secondary battery of the present invention can be prepared from a silicon-asphalt composite containing nano-silicon particles and high-softening point asphalt. In this case, preferably, the average particle size (D50) of the nano-silicon particles is less than 150nm, and the lower limit of the average particle size (D50) is not particularly limited, but considering the nano-silicon particles commonly used in the technical field to which the present invention belongs, it is preferably about 50nm or more. The softening point of the high-softening point asphalt can be 200-300°C, and preferably, the average particle size (D50) of the high-softening point asphalt is 0.5-2μm. If the average particle size is less than 0.5μm and the size of the asphalt is too small, the porosity of the silicon-carbon composite finally prepared after carbonization will be reduced. If the average particle size is greater than 2μm and the size of the asphalt is too large, there will be a problem that the pores of the silicon-carbon composite finally prepared after carbonization are too large.
[0039] In particular, the silicon-carbon composite of the present invention is characterized in that it contains pores generated by carbonization of the high softening point pitch, and it is confirmed through experiments that the average diameter of the pores is preferably 0.2 μm or more, which can be most suitable for improving the performance of secondary batteries when it is applied as a negative electrode material for secondary batteries. In addition, in the final prepared silicon-asphalt composite, the pores depend on the size of the asphalt, for example, the average particle size (D50) of the final prepared silicon-carbon composite can be 3 to 10 μm, for example, it can be 6 to 10 μm.
[0040] Preferably, the "average diameter" of the pores is less than 1 / 10 of the average particle size (D50) of the silicon-carbon composite. Preferably, the "maximum diameter" of the pores is less than 1 / 2 of the average particle size (D50) of the silicon-carbon composite. If the above conditions are not met, pores cannot be evenly formed around the silicon particles. When used as a negative electrode material for a secondary battery, the expansion of silicon cannot be effectively controlled when the secondary battery is charged, thereby reducing the efficiency and life of the secondary battery.
[0041] For example, preferably, the porosity of the pores of the silicon-carbon composite is 20% to 50%, for example, preferably, 30% to 40%. It has been confirmed through experiments that when the conditions of the size of the pores are met while satisfying the range of the porosity, it can be most suitable for improving the performance of the secondary battery when used as a negative electrode material for a secondary battery.
[0042] For example, preferably, the surface area (BET) of the silicon-carbon composite is 10 to 30 m 2 / g, for example, preferably, 15 to 30 m 2 / g, preferably, for example, 18 to 25 m 2 / g. If the surface area is less than 10m 2 / g, the initial efficiency will be reduced due to the small contact area with the electrolyte when used in secondary batteries. 2 / g, when applied to secondary batteries, a large amount of solid electrolyte interphase layer (SEI layer) is easily formed due to the increased contact area with the electrolyte, which leads to the problem of shortening the life of the secondary battery due to rapid consumption of the electrolyte.
[0043] For example, preferably, the tap density of the silicon-carbon composite is 0.5 to 1 g / cm 2 , for example, preferably, 0.5 to 0.8 g / cm 2 If the tap density is less than 0.5 g / cm 2 , the energy density will be reduced, and the battery capacity will be reduced relative to the same volume when used in secondary batteries. If the tap density is greater than 1g / cm 2 , which reduces the porosity. If applied to secondary batteries, the life of the secondary batteries will be shortened due to insufficient space for silicon expansion during charge and discharge of the secondary batteries.
[0044] Furthermore, the silicon-carbon composite can be used as a negative electrode material for a secondary battery, and thus the present invention can provide a negative electrode material for a secondary battery including the silicon-carbon composite and a secondary battery including the same.
[0045] Preparation method of silicon-carbon composite for secondary battery negative electrode material
[0046] According to another embodiment of the present invention, a method for preparing a silicon-carbon composite for a secondary battery negative electrode material can be provided, comprising: step (a), mixing a high-softening point asphalt having a softening point of 200 to 300°C with a solvent, and preparing a pulverized asphalt slurry (slurry) having an average particle size (D50) of 0.5 to 2 μm by wet grinding; step (b), mixing silicon particles with a solvent, and preparing a nano-silicon particle slurry having an average particle size (D50) of less than 150 nm by grinding; step (c), mixing the pulverized asphalt slurry of step (a) with the nano-silicon particle slurry of step (b) to form a mixed slurry of asphalt-silicon particles; step (d), forming spherical powder particles by drying the mixed slurry of asphalt-silicon particles; and step (e), carbonizing the spherical powder particles.
[0047] In this case, preferably, the solvent is an insoluble solvent for the high softening point asphalt. If a solvent that is soluble in the high softening point asphalt is used, the density of the asphalt particles and the asphalt coated therewith will be too high because the asphalt is completely dissolved in the solvent, which will make it difficult to achieve the pore size and porosity targeted by the present invention. Specific examples of the insoluble solvent may include one or more solvents selected from ethanol, methanol, acetone, and isopropanol, but are not limited thereto.
[0048] For example, the solid content in the mixed slurry of asphalt-silicon particles formed in the step (c) can be 10 to 30 weight percent (wt%), for example, it can be 15 to 20 weight percent. If the above range is not met, there will be a problem of not being able to obtain spherical powder particles having the size and size distribution targeted by the present invention.
[0049] In order to form the silicon-containing slurry into spherical powder particles, the step (d) can be performed as a drying step. In this case, the object to be generated can be a silicon-asphalt composite. In the step (d), as long as spherical powder particles can be formed, the drying method is not particularly limited. Preferably, spray drying can be performed. Spray drying is a technology that quickly dries a liquid material with hot air to prepare it into a powder state. It can be performed using a spray dryer (Spray dryer) including a sprayer, a heater, and a dryer that micronizes the liquid material. The spray drying method can adjust the particle size, morphology, etc. through various conditions such as experimental conditions and liquid state, and is suitable for mass production. The average particle size of the prepared spherical powder particles can be selected according to the purpose of the negative electrode material used, for example, preferably, 3 to 20 μm, for example, preferably, 5 to 10 μm.
[0050] The silicon-carbon composite for the negative electrode material of the secondary battery can be finally obtained by carbonizing the mixed slurry of the high softening point asphalt and the nano-silicon particles in step (e). For example, the carbonization can be carried out in an inert gas atmosphere (for example, a nitrogen atmosphere) by heating to a temperature of 1000 to 1100°C and maintaining it for about 1 hour. In this case, the heating rate can be, for example, 5 to 10°C. Although increasing the carbonization temperature can improve the effect of removing impurities and asphalt, if it is greater than 1100°C, there is a problem of forming silicon carbide (SiC), so it is preferred to carry out carbonization at a temperature of 1000 to 1100°C.
[0051] Furthermore, after the carbonization in step (e), the proportion of silicon nanoparticles in the solid component can be, for example, 50 to 90 weight percent, for example, 60 to 80 weight percent, for example, 65 to 75 weight percent. If the proportion of silicon nanoparticles in the solid component is less than 50 weight percent, the problem of reduced capacity when used as a negative electrode material for a secondary battery and the problem of mutual coagulation and adhesion between silicon-asphalt complexes during the carbonization process due to the increase in the proportion of asphalt will occur. If the proportion of silicon nanoparticles in the solid component is greater than 90 weight percent, the problem of poor adhesion (coating) of asphalt to silicon particles will occur due to the low proportion of asphalt. As a result, when used as a negative electrode material for a secondary battery, the silicon particles are directly exposed to the electrolyte and a SEI layer is rapidly formed, thereby shortening the life of the secondary battery.
[0052] The silicon-carbon composite prepared by the method for preparing the silicon-carbon composite for a secondary battery negative electrode material as described above may have the same characteristics as those described in detail with respect to the “silicon-carbon composite for a secondary battery negative electrode material”.
[0053] Embodiments of the invention
[0054] The structure and function of the present invention are described in more detail below through the preferred embodiments of the present invention. However, these are only preferred examples of the present invention and should not be interpreted as limiting the present invention in any aspect.
[0055] I. Preparation Example: Preparation of Silicon-Carbon Composite
[0056] Example 1
[0057] 1) 530 g of high softening point pitch (HSPP, OCI, softening point 250°C) was mixed with 3000 g of ethanol and stirred for 1 hour. Then, it was put into a bead mill (UBM-1L, NANOINTECH) together with Zr beads (average diameter 0.5 mm, 2 kg) and milled at 3000 rpm for 3 hours to prepare a milled asphalt slurry. Figure 2 As shown, the average diameter (D50) of the crushed asphalt in Example 1 is 0.921 μm.
[0058] 2) Mix 600g of silicon particles (OCI, the average size of the largest particles is less than 100μm), 2700g of ethanol, and 60g of stearic acid, and stir thoroughly for 1 hour. Then, put it into a bead mill (UBM-1L, NANOINTECH) together with Zr beads (average diameter 0.5mm, 2kg) and grind it at 3000rpm for 2 hours to make the average particle size of the silicon particles less than 2μm. Then, put it into a nano mill (Nano mill) (NPM-1L, NANOINTECH) together with Zr beads (average diameter 0.1mm, 2kg) and grind it at 3000rpm for 4 hours to make the average particle size of the silicon particles less than 150nm to prepare nano silicon particle slurry. Figure 3 As shown, the average diameter (D50) of the nano-silicon particles of Example 1 is 0.111 μm.
[0059] 3) Use a homogenizer to mix 80 g of the crushed asphalt slurry prepared in 1) and 2) (the weight of the crushed asphalt is 15 g) with 100 g of nano-silicon particle slurry to prepare an asphalt-silicon particle mixed slurry, and add 110 g of ethanol to make the solid content in the mixed slurry 20 weight percent.
[0060] 4) The slurry prepared in 3) is prepared into liquid drops by spray drying using a spray dryer with a two-fluid nozzle (2.4 bar) at an in-let air temperature of 100°C and a flow rate of 30 ml / min, and then the solvent of the liquid drops is evaporated to obtain a silicon-asphalt composite as spherical powder particles with an average diameter of 3 to 10 μm.
[0061] 5) Next, the temperature was raised to 1000-1100° C. at a rate of 5° C. in a nitrogen atmosphere and then maintained for 1 hour for carbonization to finally prepare a silicon-carbon composite. In this case, the content of silicon nanoparticles in the solid component was 70 weight percent.
[0062] The cross section of the silicon-carbon composite of Example 1 was observed using a scanning electron microscope. The scanning electron microscope images taken at different magnifications were as follows: Figures 4 to 6 shown.
[0063] Comparative Example 1
[0064] A silicon-carbon composite was prepared in the same manner as in Example 1, except that the following 1') was used to replace the preparation of completely pulverized asphalt in a solvent when preparing the slurry in 1) to prepare pulverized asphalt with a smaller average particle size.
[0065] 1') Mix 530g of high softening point asphalt (OCI, softening point 250°C) with 3000g of ethanol and stir thoroughly for 1 hour. Then, put it into a bead mill (UBM-1L, NANOINTECH) together with Zr beads (average diameter 0.5mm, 2kg) and grind it at 3000rpm for 3 hours. Then, put it into a nano mill (NPM-1L, NANOINTECH) together with Zr beads (average diameter 0.1mm, 2kg) and grind it at 3000rpm for 4 hours to make the average particle size (D50) of silicon particles less than 0.5μm to prepare the crushed asphalt slurry. The actual measured results are as follows Figure 7 As shown, the average particle size (D50) of the pulverized asphalt of Comparative Example 1 is 0.182 μm.
[0066] The cross section of the silicon-carbon composite of Comparative Example 1 was observed using a scanning electron microscope. The scanning electron microscope image taken is as follows: Figure 8 shown.
[0067] Example 2
[0068] A silicon-carbon composite was prepared in the same manner as in Example 1, except that the crushed asphalt slurry of Example 1 and the crushed asphalt slurry of Comparative Example 1 were mixed at a ratio of 1:1. The size of the asphalt of Example 2 was 0.5515 μm, which was the average of the size of the asphalt of Example 1 (0.921 μm) and the size of the asphalt of Comparative Example 1 (0.182 μm).
[0069] The silicon-carbon composite of Example 2 was observed using a scanning electron microscope. The scanning electron microscope image taken is as follows: Fig. 9 shown.
[0070] Comparative Example 2
[0071] The silicon-carbon composite was prepared in the same manner as in Example 1, except that the slurry preparation in 3) was replaced by 3'), and the difference was that the asphalt was completely dissolved. Specifically, ethanol, which is an insoluble solvent for asphalt, was used in Example 1, and tetrahydrofuran (THF) was used as a soluble solvent for asphalt in Comparative Example 2. Therefore, in Comparative Example 2, the silicon-carbon composite was prepared by completely dissolving the asphalt in a solvent and then drying it to coat the nano-silicon particles.
[0072] 3') After completely dissolving 80 g of the crushed asphalt slurry prepared in 1) (the weight of the crushed asphalt is 15 g) in 150 g of THF, 100 g of the nano-silicon particle slurry prepared in 2) is added thereto and mixed using a homogenizer to prepare an asphalt-silicon particle mixed slurry such that the solid content in the mixed slurry is 20 weight percent.
[0073] After the processes 4) and 5) in Comparative Example 2, the content of silicon nanoparticles in the solid component finally prepared was 70 weight percent.
[0074] The cross section of the silicon-carbon composite of Comparative Example 2 was observed using a scanning electron microscope, and the scanning electron microscope image taken was as follows: Fig.10 shown.
[0075] II. Experimental Example: Determination of Surface Properties of Silicon-Carbon Composites
[0076] The surface area, tap density, pore size and porosity of the silicon-carbon composites of Examples 1 and 2 and Comparative Examples 1 and 2 were measured and the results are shown in Table 1. In this case, the surface area was measured according to ASTM D-6556, and the measurement methods of other values are as described below.
[0077] Measurement method 1: Surface area (BET) and tap density (Tap density)
[0078] The surface area (BET) of the silicon-carbon composite was measured using a specific surface area analyzer (Belsorp-max, manufactured by BEL Japan Co., Ltd.) according to STM D-6556.
[0079] 30 g of the sample was placed in a 100 ml measuring cylinder and tapped for 10 minutes using a tap density meter (JV2000, manufactured by Copley). After reading the scale, the sample was tapped again for 10 minutes. This operation was repeated until the volume change was within 2% to measure the tap density.
[0080] Measurement Method 2: Pore Size and Porosity
[0081] In the scanning electron microscope image (50,000 times) of the cross section of the silicon-carbon composite, a line was drawn on the particles of the finally prepared silicon-carbon composite using the "Image J" program, and the length of the pores of the silicon-carbon composite that touched the line was measured and recorded (the "part that is not a cross section, that is, a blank or three-dimensional part" was determined as a pore). Draw more than 5 lines so that they are spaced at a predetermined interval and do not overlap each other. The average value of the measured pore lengths was taken as the pore size.
[0082] The porosity (%) was calculated as a percentage of a value obtained by dividing the "total length of lines" drawn on particles of the finally prepared silicon-carbon composite by the "total of measured pore lengths".
[0083] Measurement method 3: Measurement of the average particle size (D50) of the final silicon-carbon composite
[0084] The silicon-carbon composite finally prepared was used as a negative electrode material. The average particle size D50 (μm) of the composite was measured using an LS13 320 Laser Diffraction Particle Size Analyzer (manufactured by BECKMAN COULTER) as a particle size analyzer. The results are shown in Table 1 below.
[0085] Table 1
[0086]
[0087] It can be seen from Table 1 that the surface area (BET) values of the silicon-carbon composites of Example 1 and Comparative Example 1, which have similar preparation methods and similar porosities, are similar, but the pore size and porosity of Comparative Example 2, in which asphalt is dissolved in a solvent to form a spheroid, are too small, and the surface area value is also low.
[0088] Furthermore, it can be seen that the size of the pores is proportional to the size of the asphalt, and the porosity is also proportional to the size of the asphalt, but there is not much difference. In the case of using crushed asphalt, the tap density is about 0.62 g / cm 3 In the case of Comparative Example 2 prepared by dissolving asphalt in a solvent, the tap density was measured to be 0.64 g / cm due to the low porosity. 3 higher value.
[0089] III. Half-Cell Test
[0090] In order to analyze the electrochemical properties of negative electrode materials for secondary batteries, the silicon-carbon composites prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were used as negative electrode materials. A negative electrode plate using the silicon-carbon composite powder as an active material was prepared. The negative electrode plate was prepared by casting a slurry in which the active material, the conductive material (Imerys Graphite & Carbon, Super-P) and the binder were mixed in a weight ratio of 94:1:5 on copper foil. In this case, CMC and SBR were mixed in a weight ratio of 3:7 as a binder. The prepared negative electrode plate was prepared as a button cell using lithium metal (Li metal) as the relative electrode to confirm the electrochemical properties. The charge and discharge conditions were charging CC / CV: 0.01V / 0.01C, discharging CC1.5V, and a flow rate of 0.2C.
[0091] The initial charge efficiency (ICE), initial charge capacity (ICC), and initial discharge capacity (IDC) were measured using a half-cell device, TOSCAT-3100, and the results are shown in Table 2 below.
[0092] Furthermore, the life characteristics (specific capacity at 50 cycles) were measured, and the results are shown in Table 2 and Table 3. Fig.11 (Vertical axis: specific capacity after 50 cycles, horizontal axis: number of cycles)
[0093] In addition, the percentage (%) value of the specific capacity after 50 cycles divided by the initial discharge capacity (IDC) is shown in the following Table 2. This is used to confirm whether the life characteristics are still maintained compared to the initial discharge capacity after 50 cycles. The higher the value, the better the life characteristics.
[0094] Table 2
[0095]
[0096] According to Table 2 and Fig.11 It is found that when the silicon-carbon composites of Examples 1 and 2 of the present invention are used as negative electrode materials, the battery performance, especially the battery life, is better than that of Comparative Examples 1 and 2.
[0097] The present invention is described above with reference to the illustrated drawings, but the present invention is not limited to the embodiments and drawings disclosed in this specification, and a person skilled in the art of the present invention can implement various modifications within the scope of the technical concept of the present invention. At the same time, in the description of the above embodiments of the present invention, even if the effects brought about by the structure of the present invention are not clearly described, the effects predicted by the related structure should also be recognized.
Claims
1. A silicon-carbon composite for a negative electrode material of a secondary battery, characterized in that: It is formed by a silicon-asphalt composite containing nano-silicon particles and high softening point asphalt. The average particle size D50 of the nano-silicon particles is less than 150 nm. The high softening point asphalt has a softening point of 200 to 300°C. The average particle size D50 of the high softening point asphalt is 0.5 to 2 μm.
2. The silicon-carbon composite for secondary battery negative electrode material according to claim 1, characterized in that: comprising pores produced by carbonization of the high softening point pitch, The average diameter of the pores is 0.2 μm or more, which is less than 1 / 10 of the average particle diameter D50 of the silicon-carbon composite. The maximum diameter of the pores is less than 1 / 2 of the average particle diameter D50 of the silicon-carbon composite. The average particle size D50 of the silicon-carbon composite is 3 to 10 μm.
3. The silicon-carbon composite for secondary battery negative electrode material according to claim 1, characterized in that: The porosity of the pores is 20% to 50%.
4. The silicon-carbon composite for secondary battery negative electrode material according to claim 1, characterized in that: Surface area BET 10~30m 2 / g, tap density is 0.5~1g / cm 2 .
5. The silicon-carbon composite for secondary battery negative electrode material according to claim 2, characterized in that: The average particle size D50 of the silicon-carbon composite is 6 to 10 μm.
6. A negative electrode material for a secondary battery, characterized in that: A silicon-carbon composite for a negative electrode material for a secondary battery comprising the silicon-carbon composite for a negative electrode material according to any one of claims 1 to 5.
7. A secondary battery, characterized in that: A silicon-carbon composite for a negative electrode material for a secondary battery comprising the silicon-carbon composite for a negative electrode material according to any one of claims 1 to 5.
8. A method for preparing a silicon-carbon composite for a negative electrode material of a secondary battery, characterized in that: include: Step (a), mixing high softening point asphalt with a softening point of 200 to 300° C. with a solvent, and preparing a crushed asphalt slurry having an average particle size D50 of 0.5 to 2 μm by wet crushing; Step (b), mixing silicon particles with a solvent, and then crushing to prepare a nano silicon particle slurry having an average particle size D50 of less than 150 nm; Step (c), mixing the crushed asphalt slurry of step (a) with the nano silicon particle slurry of step (b) to form a mixed slurry of asphalt-silicon particles; Step (d), forming spherical powder particles by drying the mixed slurry of pitch-silicon particles; as well as Step (e), carbonizing the spherical powder particles.
9. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 8, characterized in that: The solvent is an insoluble solvent for the high softening point asphalt.
10. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 9, characterized in that: The insoluble solvent includes at least one selected from the group consisting of ethanol, methanol, acetone, and isopropanol.
11. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 8, characterized in that: The solid content of the mixed slurry of asphalt and silicon particles formed in the step (c) is 10 to 30 weight percent.
12. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 11, characterized in that: After the carbonization in step (d), the proportion of silicon nanoparticles in the solid component is 50 to 90 weight percent.
13. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 8, characterized in that: The drying in step (d) is performed by spray drying.
14. The method for preparing the silicon-carbon composite for secondary battery negative electrode material according to claim 8, characterized in that: The carbonization is carried out at a temperature of 1000-1100°C.
15. A silicon-carbon composite for a negative electrode material of a secondary battery, prepared by the preparation method according to any one of claims 8 to 14, characterized in that: The silicon-carbon composite for negative electrode material contains pores generated by carbonization of high softening point pitch, The average diameter of the pores is 0.2 μm or more, which is less than 1 / 10 of the average particle diameter D50 of the silicon-carbon composite. The maximum diameter of the pores is less than 1 / 2 of the average particle diameter D50 of the silicon-carbon composite. The average particle size D50 of the silicon-carbon composite is 3 to 10 μm.
16. The silicon-carbon composite for secondary battery negative electrode material according to claim 15, characterized in that: The porosity of the pores is 20% to 50%.